Artificial intelligence in education: integrating serious gaming into the language class classdojo technology for classroom behavioral management - Yassine Benhadj; Mohammed El Messaoudi; Abdelhamid Nfissi (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
The aim of the study at hand was to examine students' perceptions of game elements used in gamification application. ClassDojo, as a study case, was implemented class-wide in a Moroccan High School EFL classroom. Data was gathered and saved directly through the application. It is qualitative research that opted for structured interviews to collect data. The findings were evaluated in so far as class motivation, participation, cooperation, discipline, attendance, and classroom discourse are concerned. This study has shown a crystal clear improvement in terms of discipline, motivations and classroom participation, suggesting the great need to conduct more research with a view to determine if these areas could be positively or negatively impacted when integrating ClassDojo in classroom management on a large scale. The findings of this study are of much significance to decision makers, curriculum developers, syllabus designers, and teachers in both senior and junior schools in Morocco.